Development of Interactive e-modules Based on Local Wisdom Using Android to Improve Students' Higher Order Thinking Skills (HOTS) - Lalu Usman Ali; Muhammad Zaini (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to test the feasibility of an interactive e-module based on local wisdom using an Android application to increase students' HOTS in circular motion material according to teachers and lecturers and analyze the increase in students' HOTS abilities after using an interactive e-module based on local wisdom using an Android application. This research is development research by applying the 4-D model. The development procedure consists of 4 stages, namely; define, design, develop, and disseminate. This research was carried out at MAN 1 Mataram, MAN 1 Central Lombok, MAN 1 West Lombok and MAN 1 East Lombok. This research instrument consists of a HOTS capability assessment instrument, an interactive E-module feasibility assessment instrument based on local wisdom, and an Android application media feasibility instrument. The results of this research are that this learning tool is suitable for use in physics learning to increase students' HOTS in the good and very good categories as tested by lecturers and physics teachers; This learning tool is able to increase students' HOTS within one group (pretest-posttest) and between groups (experiment-control). Data obtained from mixed ANOVA analysis in the experimental class showed that the increase in HOTS ability was more significant than the increase in HOTS in the control group; and there are differences in the HOTS abilities of students who use local wisdom-based e-module learning devices assisted by Android applications and students who use teacher teaching materials.